Zatrucie cisem – patofizjologia, obraz kliniczny, leczenie oraz perspektywy użycia emulsji tłuszczowych - Rutkiewicz, Aleksander; Schab, Paweł; Kubicius, Andrzej; Szeremeta, Filip; Małysz, Franciszek; Dadok, Janusz; Misiewska-Kaczur, Agnieszka (Anestezjologia Intensywna Terapia, 2019)
The article presents pathophysiology, clinical picture and management of yew poisoning. Authors present also their own experiences with treating yew poisoning with fat emulsion. Plants of the yew genus, of which in Europe predominates Taxus baccata, are well known for their toxic properties. Particularly high concentrations of poisonous alkaloids are present in the needles of this evergreen and highly popular decorative plant. The danger associated with accidental or intentional ingestion of yew is primarily related to the cardiotoxic effects of the alkaloids (taxine A and B). Taxine B shows a much stronger toxic effect on the heart than taxine A. It affects atrio-ventricular conduction, what may result in a widening of the QRS complexes, atrio-ventricular blocks (A-V) of II/ III degree and even in asystole. Yew poisoning is relative rare and evidence-based treatment guidelines on management of such poisoning is hard to prepare. The first-line treatement should base on suportive therapy. In some cases extracorporeal life support therapies such veno-arterial ECMO should be consider. There are also premise based on case reports and mechanism of action that the use of fat emulsion may be effective rescue treatment.